Intracellular trafficking of the human cytomegalovirus-encoded 7-trans-membrane protein homologs pUS27 and pUL78 during viral infection: a comparative analysis - Niemann, Ina; Reichel, Anna; Stamminger, Thomas (Viruses, 2014)
Human cytomegalovirus (HCMV) encodes four G protein-coupled receptor (GPCR) homologs, termed pUS27, pUS28, pUL33, and pUL78. In contrast to the extensively characterized vGPCRs pUS28 and pUL33, knowledge concerning pUS27 and pUL78 is limited. Previous studies already demonstrated constitutive internalization of pUS27 and pUL78, as well as an association with the endosomal machinery, however, these results were mainly obtained using transiently transfected cells. To explore the subcellular localization of both receptors during viral infection, we constructed recombinant HCMVs expressing tagged vGPCRs. Colocalization analyses revealed a predominant association of pUS27 or pUL78 with the trans-Golgi network or the endoplasmic reticulum, respectively. Intriguingly, our data emphasize that protein sorting is highly regulated by viral functions as we detected dramatic changes in the colocalization of pUS27 and pUL78 with endosomal markers during progression of HCMV replication. Furthermore, we observed cell type-dependent differences in trafficking of both vGPCRs between fibroblasts and epithelial cells. Most importantly, infection experiments with a recombinant HCMV carrying tagged versions of pUS27 and pUL78 simultaneously, revealed that these two proteins do not colocalize during viral infection. This contrasts to results of transient expression experiments. In conclusion, our results highlight the importance to investigate vGPCR trafficking in a viral context.
EVALuna2:8228